Penerapan Konsep Value Engineering pada Proyek Bangunan Gedung Sekolah : (Studi Kasus: Madrasah Ibtidaiyah Negeri 3 Gunungsitoli) - Ryobi Irfanto; Iwan Saputra N W; Hans Dermawan (Universitas Kristen Maranatha, 2023)
The cost aspects of construction projects are very diverse, such as overbudget, overtime, etc. which are grouped as unnecessary costs. The concept of value engineering can optimize the unnecessary costs. Value engineering is a technique for analyzing job functions or processes to determine